Engineering students’ motivation towards the involvement in volunteerism - Azrol bin Abdullah, Rosmahalil; Hasril bin Amiruddin, Mohd; binti Abdul Kadir, Zulida; binti Kamarulzaman, Robijah; ., . (International Journal of Engineering and Technology, 2018)
This study aims to examine the students’ motivation towards their involvement in volunteer activities. 399 students of Universiti Tun Hussein Onn Malaysia were selected as the samples of this study. This study employs the Volunteer Function Inventory (VFI) by Clary et.al. (1998). The findings were analysed using the IBM SPSS Statistics (Statistical Packages for Social Sciences) Version 22. The pilot study was conducted and the Alpha Cronbach value was 0.835. The results showed that the function of “understanding” (mean = 5.41) was the most dominant influence on respondents' perceptions towards volunteer activities. The findings also found that there was a weak positive relationship between the motivational function and the student's academic achievement. In addition, several research proposals are presented to further enhance the concepts of appreciation and sustainability in volunteer activities.
Keywords: Volunteerism; Motivation; Volunteer Functions Inventory (VFI); Academic Achievement